Comparative Analysis of the Oocytes and Early Development of Two Species of Curimatidae Teleost Fish. (14th May 2012) - Perini, V. R.; Sato, Y.; Rizzo, E.; Bazzoli, N.
Summary Curimatella lepidura and Steindachnerina elegans are small forage fish, constituting an important link in the food chain, serving as food for larger commercial fish. In this study, characteristics of the eggs, of the oocyte's surface ultrastructure and of the embryogenesis are first described for these species. Absolute fecundity was 40864 ± 8769 oocytes for C. lepidura and 22089 ± 8710 oocytes for S. elegans. Oocytes of both species are yellowish, weakly adhesive and with a post‐fertilization diameter of 1019.5 ± 20.6 μm and 978.75 ± 29.16 μm for C. lepidura and S. elegans, respectively. The ultrastructural analysis, using scanning electron microscopy, showed that the oocyte's surface of both species has pore canals over the entire surface and a funnel‐shaped micropyle. At 24°C, the embryonic development of C. lepidura was completed 25 h after fertilization, and blastopore closure occurred in 7 h 30 min. In S. elegans, larvae hatched 20 h after fertilization, and blastopore closure occurred in 7 h 15 min. The fertilization rate was 74.5 ± 7.96 and 71.2 ± 10.8% for C. lepidura and S. elegans, respectively. This study provides important support for clarifying phylogenetic relationships and in ecological and zoological understanding of Neotropical Curimatidae fish.